SELF-DESCRIPTIVENESS OF ULTRASONOGRAPHY IN THE DIFFERENTIAL DIAGNOSTICS OF CYST OF THE LATERAL NECK AREA - Ткаченко, П.І.; Резвіна, К.Ю. (World of Medicine and Biology, 2015)
This paper presents the features of ultrasound examination of cysts at the lateral areas of the neck. Based on the results and analysis it was found that in this area often localized cysts, each of which has its own specific features and sonographic structure can be divided into branhiohenni, epidermoid, dermoid and cysts of the salivary glands, which later was confirmed in morphological study material. This shows high diagnostic informative method of examination and which deserves wider use in everyday clinical practice in patients with tumors and tumor formations neck.